2020
DOI: 10.1186/s40942-020-00244-x
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on retina education through social media

Abstract: Since the beginning of the Internet, new ways of providing medical education have emerged. Social media networks are one of the most influential communication tools and allow content sharing, collaborative modification and interaction. Its relevance for teaching and learning in medical education has been extensively studied. These new media have also heightened the need for a new way of communication. The purpose of this article is to discuss the value of communication in medical education through social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While students have reported a strong preference for in‐person tuition, 67 social media offers numerous paedagogical options, including sharing of instructive clinical images and videos, as exemplified by the Instagram account, @the.eyedoc, 68 or in interactive tutorials hosted on networking sites 69 . A paucity of evidence for effectiveness of teaching ophthalmology over social media has been emphasised 70 . One study conducted at Khawaja Muhammad Safdar Medical College, Pakistan, showed that lectures and supporting materials shared on Facebook and WhatsApp, combined with guided interactive discussions, achieved significant learning based on pre‐ and post‐test assessments 71 .…”
Section: Applications Of Social Media In Ophthalmic Education Trainin...mentioning
confidence: 99%
“…While students have reported a strong preference for in‐person tuition, 67 social media offers numerous paedagogical options, including sharing of instructive clinical images and videos, as exemplified by the Instagram account, @the.eyedoc, 68 or in interactive tutorials hosted on networking sites 69 . A paucity of evidence for effectiveness of teaching ophthalmology over social media has been emphasised 70 . One study conducted at Khawaja Muhammad Safdar Medical College, Pakistan, showed that lectures and supporting materials shared on Facebook and WhatsApp, combined with guided interactive discussions, achieved significant learning based on pre‐ and post‐test assessments 71 .…”
Section: Applications Of Social Media In Ophthalmic Education Trainin...mentioning
confidence: 99%
“…With demographic breakdowns showing prevalent Twitter use by ophthalmologists in training and early in their careers, social media will likely only grow as an academic presence going forward into the future. A discussion of retina education concluded that visual social media posts could educate medical students and ophthalmology trainees more effectively and accessibly than other formats, so the use of these networks might evolve from simply supplemental content to a key mode for education [26]. More concretely, a review of social media in graduate-level medical education indicated increasing adoption of social media to supplement traditional learning methods in these programs, from Twitter or specialty-specific blogs becoming the site for journal clubs to YouTube videos (or in the case of ophthalmology, EyeTube) demonstrating operating room techniques [27].…”
Section: Contributions Of Social Media To Academiamentioning
confidence: 99%
“…Within the surgical training scenario, with rapid and constant changes in vitreoretinal surgeries, social media offers opportunities for teaching, training, research, and social interaction. Recent studies have reported the use of social media among retinal specialists (10,11) . However, information on how vitreoretinal surgeons and fellows have used surgical video recordings as a complementary teaching aid in the field is lacking.…”
Section: Introductionmentioning
confidence: 99%